Expression of the T-cell regulatory marker FOXP3 in primary cutaneous large B-cell lymphoma tumour cells - Felcht, Moritz; Heck, Markus; Weiß, Christel; Nicolay, Jan Peter; Booken, Nina; Goerdt, Sergij; Klemke, Claus-Detlev (British journal of dermatology, 2012)
BACKGROUND: Primary cutaneous B-cell lymphomas (PCBCL) are subdivided into the aggressive form, primary cutaneous diffuse large B-cell lymphoma, leg type (PCLBCL, LT) and two subtypes of indolent behaviour (primary cutaneous follicle centre lymphoma and primary cutaneous marginal zone B-cell lymphoma). The difference in clinical behaviour can be explained by the tumour cell itself, or the lymphoma microenvironment including the antitumour immune response. OBJECTIVES: To investigate the presence of regulatory T cells (Treg), CD4+CD25+FOXP3+, in the microenvironment of PCBCL in correlation with clinical outcome. METHODS: Tumour specimens of 55 consecutive cases of PCBCL were blinded and analysed for FOXP3, CD4 and CD25 expression by immunohistochemistry. Confocal images were taken with a Leica SP5. Statistical analyses were performed to determine significance. The test was considered significant when P<0.05. RESULTS: The CD4 and FOXP3 expression as well as the CD4/FOXP3 ratio were significantly increased in PCBCL of indolent behaviour in contrast to PCLBCL, LT (P=0.0002 for CD4, P<0.0001 for FOXP3 and P=0.0345 for FOXP3/CD4 ratio). CD25 expression did not differ in the three groups (P=0.9414). Within the group of patients with PCLBCL, LT we identified a subgroup with FOXP3+ tumour cells as demonstrated by CD20/FOXP3 double stainings. Patients with FOXP3+ PCLBCL, LT tumour cells showed a better prognosis on Kaplan-Meier analysis. CONCLUSION: High numbers of Treg in the lymphoma microenvironment correlate with a better prognosis in PCBCL. In PCLBCL, LT the presence of FOXP3+ tumour cells is beneficial for prognosis suggesting that FOXP3 expression of PCLBCL, LT tumour cells might serve as a tumour suppressor.